Anterior Hypopituitarism and Treatment Response in Hunter Syndrome: A Comparison of Two Patients. (28th November 2016) - Nour, Munier A.; Luca, Paola; Stephure, David; Wei, Xing-Chang; Khan, Aneal
Abstract : Hypopituitarism is a clinically important diagnosis and has not previously been reported in Hunter syndrome. We contrast two cases with anatomic pituitary anomalies: one with anterior panhypopituitarism and the other with intact pituitary function. Patient 1, a 10-year-old boy with Hunter syndrome, was evaluated for poor growth and an ectopic posterior pituitary gland. Endocrine testing revealed growth hormone (GH) deficiency, secondary adrenal insufficiency, and tertiary hypothyroidism. An improvement in growth velocity with hormone replacement (GH, thyroxine, and corticosteroid) was seen; however, final adult height remained compromised. Patient 2, a 13-year-old male with Hunter syndrome, was evaluated for growth failure. He had a large empty sella turcica with posteriorly displaced pituitary. Functional endocrine testing was normal and a trial of GH-treatment yielded no significant effect. Panhypopituitarism associated with pituitary anomalies has not been previously reported in Hunter syndrome and was an incidental finding of significant clinical importance. In the setting of documented anterior hypopituitarism, while hormone replacement improved growth velocity, final height remained impaired. In patient 2 with equivocal GH-testing results, treatment had no effect on linear growth. These cases highlight the importance of careful clinical assessment in Hunter syndrome and that judicious hormone replacement may be indicated in individual cases.